PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP MOTIVASI DAN KINERJA KARYAWAN HOTEL FAVOR MAKASSAR - Feby Febrianingsih; Mahlia Muis; Jumidah Maming (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
Every leader can exert influence towards his subordinates. This research aims to know the influence of leadership and compensation of employee motivation and performance against the Favor hotel Makassar. This research approach is quantitative, and this type of research is the causality. There are 2 types of data, namely data qualitative and quantitative data, whereas data source using primary data and secondary data. This research used 4 methods of data collection method, the method of observation questionnaire (question form), interviews, and method of study documentation. Qualitative analysis is a method that aims to transform a collection of raw data into a form that is easy to understand, in the form of a concise information, where research results and their analysis are outlined in a scientific writings which of the analysis It will be formed a conclusion. The results showed that (1) the variable compensation effect on leadership and employee motivation variables Hotel Makassar's Favor. (2) The compensation and leadership Variables have no effect against variable employee performance Hotel Makassar's Favor. (3) the motivational and leadership Variables take effect directly against variable employee performance through motivation variables Hotel Makassar's Favor. (4) Variable compensation effect indirectly against variable employee performance through motivation variables Hotel Makassar's Favor.